A Double-Side Cooled SiC MOSFET Power Module With Sintered-Silver Interposers: I-Design, Simulation, Fabrication, and Performance Characterization - Ding, Chao; Liu, Heziqi; Ngo, Khai D. T.; Burgos, Rolando; Lu, Guo-Quan (IEEE transactions on power electronics, 2021)
Planar, double-side cooled power modules are emerging in electric-drive inverters because of their low profile, better heat extraction, and lower package parasitic inductances. However, there is still a concern about their reliability due to the rigid interconnection between the device chips and two substrates of the power module. In this article, a porous interposer made of low-temperature sintered silver is introduced to reduce the thermomechanical stresses in the module. A double-side cooled half-bridge module consisting of two 1200 V, 149 A SiC MOSFETs was designed, fabricated, and characterized. By using the sintered-Ag instead of solid copper interposers, our simulation results showed that, at a total power loss of 200 W, the thermomechanical stress at the most vulnerable interfaces (interposer-attach layer) was reduced by 42% and in the SiC MOSFET by 50% with a tradeoff of only 3.6% increase in junction temperature. The sintered-Ag interposers were readily fabricated into the desired dimensions without postmachining and did not require any surface finishing for die bonding and substrate interconnection by silver sintering. The porous interposers were also deformable under a low force or pressure, which helped to accommodate chip thickness and/or substrate-to-substrate gap variations in the planar module structure, thus simplifying module fabrication. The experimental results on the electrical performance of the fabricated SiC modules validated the success of using the porous silver interposers for fabricating planar, double-side cooled power modules.